Capoeira: fight, game or dance? The impact of the curricular matrix of the course of physical education in the university perception - Souza, Michel Kendy (2017)
The aim of this study was to investigate the influence of different under graduation curriculum adopted by universities on capoeira's concept among Physical Education students, as well as its acceptance as a curricular component. 60 male and female students were subjects of the study, a questionnaire were applied for data collection. The higher frequencies answers for capoeira concept were fight (33.3%), game (23.5%) and dance (16.6%). Approximately 75% said that would like to have capoeira as discipline of physical education course. It was verified that the undergraduate curriculum directly influence university students on the capoeira's concept. The capoeira discipline is still not inserted in most of the studied universities, however there are higher acceptance by students to include this modality in Physical Education course.